1991
DOI: 10.1111/j.1365-3091.1991.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Rock varnish in the Sonoran Desert: microbiologically mediated accumulation of manganiferous sediments

Abstract: Rock varnish occurs in virtually all environments, most commonly in arid and semi‐arid climates, including Antarctica. Rock varnish consists of thin layers of intimately mixed aeolian and chemical sediments often showing botryoidal and more rarely stromatolite‐like morphologies. Typical rock varnish samples collected at Twin Peak Mountain Park, near Phoenix, Arizona, consist of abundant quartz, with plagioclase, illite and a mixed layer, Fe‐clay mineral, probably corrensite. EDS, SEM (BSE) and TEM analyses rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Numerous studies identified incorporated clay minerals in aerially exposed silica-rich coatings (e.g. Potter and Rossman, 1977;Dorn and Oberlander, 1982;Nagy et al, 1991;Krinsley, 1998;Perry et al, 2006). On the contrary, only a few synthesis experiments showed that clay minerals can form in situ in a silica-rich matrix.…”
Section: Role Of Sulfates In the Formation Of The Coatingsmentioning
confidence: 95%
“…Numerous studies identified incorporated clay minerals in aerially exposed silica-rich coatings (e.g. Potter and Rossman, 1977;Dorn and Oberlander, 1982;Nagy et al, 1991;Krinsley, 1998;Perry et al, 2006). On the contrary, only a few synthesis experiments showed that clay minerals can form in situ in a silica-rich matrix.…”
Section: Role Of Sulfates In the Formation Of The Coatingsmentioning
confidence: 95%
“…Analyses of 'bulk samples' (i.e., those requiring the scraping of varnish and underlying weathering rind and rock material) have included analysis of amino acids (Warsheid, 1990;Nagy et al, 1991;Perry and Kolb, 2003;, isotopic analysis (Dorn and DeNiro, 1985), analysis of fatty acid methyl esters (Schelble et al, 2005), phospholipid fatty acids (Kuhlman et al, 2006a), and extraction of genetic material for phylogenetic insight (Eppard et al, 1996;Kuhlman et al, 2005;Spilde et al, 2005;Benzerara et al, 2006;Kuhlman et al, 2006a,b;Northup et al, 2010).…”
Section: Towards Resolving the Contradiction Of Dna Versus Cultural Amentioning
confidence: 98%
“…Endolithic Bacillus spp. have been obtained from a wide variety of sites within the lithosphere, such as the interiors of mined amber (6), halite crystals (58), marine manganese nodules (36), rock varnishes from Sonoran, Mohave, and Negev desert rocks (23,35,45), deep subsurface boreholes (2,4), Sonoran desert basalts (3), and Florida limestones from intertidal zones (1). In addition, several Bacillus spp.…”
mentioning
confidence: 99%